Sex-specific prognostic utility of the sarcopenia index in all-cause mortality risk for patients with heart failure - Li, Ming; Liang, Yanying; Wu, Baozhen; Zhu, Ziliang; Wang, Meifang; Chen, Jianying; Chen, Can (Frontiers in Nutrition, 2025)
BackgroundThe sarcopenia index (SI), derived from serum creatinine and cystatin C levels, has emerged as a novel and accessible biomarker for predicting clinical outcomes. However, its sex-specific prognostic utility in heart failure (HF) remains poorly understood. This study aimed to investigate the association between SI and all-cause mortality in HF, with a focus on sex-specific differences.MethodsA retrospective cohort of 753 patients (median age: 69 years; 61% male) diagnosed with HF from a tertiary hospital in China was analyzed. Cox regression models and Kaplan–Meier survival analyses were utilized to evaluate the relationship between SI and all-cause mortality. Stratified analyses based on sex were performed, and the incremental predictive value of SI was assessed by integrating it into traditional risk models.ResultsOver a median follow-up of 537 days, 143 deaths occurred. In adjusted models, a lower SI was significantly associated with an increased risk of all-cause mortality in male patients (hazard ratio: 0.98 per unit increase, 95% confidence interval: 0.97–0.99, p = 0.002). Males in the lowest SI tertile had a 1.66-fold higher mortality risk than those in the highest tertile (p = 0.004). Kaplan–Meier survival analysis further confirmed these findings, demonstrating significantly lower survival probabilities for males in the lowest SI tertile than for those in higher tertiles (Log-rank p = 0.0013). No such association was observed in females. Adding SI to risk models improved prognostic accuracy in males, enhancing the C-statistic from 0.749 to 0.764 and significantly improving net reclassification and discrimination indices (p < 0.05).ConclusionThe SI serves as a robust sex-specific predictor of all-cause mortality in HF, demonstrating significant prognostic value in males but limited utility in females. These findings highlight the potential of SI as a cost-effective addition to existing risk stratification models for male patients with HF.